Implementation of the Strengthening Project for the Pancasila Student Profile and the Rahmatan Lil Alamin Student Profile as an Effort to Preserve Local Wisdom at MAS Alkhairaat Biromaru - Siti Rahma Hardiyanti; Rizka Fadliah Nur; Rahmadiani Rahmadiani (STKIP Taman Siswa Bima, 2025)
The underlying problem of this research is the decreasing attention of the younger generation toward local wisdom, which serves as an important marker of regional cultural identity. This condition requires concrete efforts from educational institutions to integrate local cultural values into the learning process. This study was conducted to examine the implementation of the P5 and PPRA projects as a strategy for preserving local wisdom at MAS Alkhairaat Biromaru. The research employed a descriptive qualitative approach, with data collected through observation, interviews, and documentation. Data analysis was carried out through the stages of data reduction, data display, and conclusion drawing. The findings indicate that the project implementation has been running well and has made a tangible contribution to the preservation of local wisdom. The main supporting factor is the strong commitment of teachers and the head of the madrasah in fostering students’ character, while the obstacles include limited time and tight academic schedules, which hinder cultural preservation activities from being conducted regularly and systematically. This research contributes by providing practical insights into the integration of Pancasila values and Islamic teachings through local wisdom-based activities, while also offering recommendations for madrasahs to develop more effective and sustainable learning strategies in preserving the nation’s cultural identity.